2017
DOI: 10.1136/bmjopen-2017-018823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of second child intent on delivery mode after Chinese two child policy implementation: a cross sectional and prospective observational study of nulliparous women in Chongqing

Abstract: ObjectivesTo assess the influence of second child intent on the delivery preferences and final delivery modes of nulliparous women, particularly caesarean delivery on maternal request (CDMR), after implementation of China’s two child policy.DesignCross sectional and prospective observational study.SettingA tertiary teaching hospital in Chongqing, China.Participants1000 low risk nulliparous women were initially involved, and were divided into two groups based on their intent on having a second child. 814 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…In this cross-sectional study we found that the rate of intent for a second child was 39.4% of 11 991 Chinese women of childbearing age. This was much lower than the rate (61.25%) recorded under the one-child policy6 and was similar to rates reported by others during the two-child policy 9 10. According to the report by the China Women’s Federation in 2017, only 20.5% of parents wanted to have a second child 9.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In this cross-sectional study we found that the rate of intent for a second child was 39.4% of 11 991 Chinese women of childbearing age. This was much lower than the rate (61.25%) recorded under the one-child policy6 and was similar to rates reported by others during the two-child policy 9 10. According to the report by the China Women’s Federation in 2017, only 20.5% of parents wanted to have a second child 9.…”
Section: Discussionsupporting
confidence: 73%
“…According to the report by the China Women’s Federation in 2017, only 20.5% of parents wanted to have a second child 9. However, Zhao and colleagues,10 in a hospital-based cross-sectional study of 814 nulliparous pregnant women in 2017, reported that 51.2% of women intended to have a second child. The discrepancy between these studies might be related to the different characteristics of the study population, as we found that economic, childrearing, and health factors were the major barriers to fertility intent.…”
Section: Discussionmentioning
confidence: 99%
“…In the stratification of the study design, the pooled proportions of preference for CS reported by women in longitudinal studies were 14% in early or middle pregnancy (95% CI 12%–17%; χ 2 = 20.42; df = 5 [ p < 0.01]; I 2 = 76%) [ 9 , 14 , 15 , 35 , 68 , 69 ] and 21% in late pregnancy (95% CI 15%–26%; χ 2 = 109.02; df = 6 [ p < 0.01]; I 2 = 94%) [ 9 , 14 , 15 , 35 , 36 , 68 , 69 ]. In cross-sectional studies, the proportions were 17% in early or middle pregnancy (95% CI 14%–20%; χ 2 = 36.61; df = 6 [ p < 0.01]; I 2 = 84%) [ 8 , 37 – 41 , 72 ], 22% in late pregnancy (95% CI 18%–25%; χ 2 = 697.67; df = 18 [ p < 0.01]; I 2 = 97%) [ 42 – 50 , 56 , 57 , 62 , 63 , 65 – 67 , 70 72 ], and 30% postpartum for the index pregnancy (95% CI 19%–40%; χ 2 = 809.43; df = 7 [ p < 0.01]; I 2 = 99%) [ 51 – 53 , 55 , 58 – 60 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six longitudinal studies [ 9 , 14 , 15 , 35 , 68 , 69 ] investigated the change of preference from early or middle pregnancy to late pregnancy, whether prospectively or retrospectively. All 6 studies reported an increase in the preference for CS as birth time approached, and the mean difference to test the change was statistically significant (mean difference 7%, 95% CI 1%–13%; χ 2 = 63.76; df = 5 [ p < 0.01]; I 2 = 92%).…”
Section: Resultsmentioning
confidence: 99%
“…Some questions remain about the impacts of the birth policy changes on maternal and infant health. To date, the impact of birth policy changes on women's reproductive decisions, delivery mode, pregnancy complications, pregnancy age, and birth outcomes has been reported [6][7][8][9][10][11]. An association between certain maternal characteristics and birth defects (BDs) has also been reported, such as maternal age, maternal parity, use of assisted reproductive technology, and diabetes mellitus [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%